UJI AKTIVITAS ANTIBAKTERI MASKER GEL PEEL OFF EKSTRAK DAUN PLETEKAN (Ruellia tuberosa L.) TERHADAP Staphylococcus aureus - Mighfar Syukur; Ahmad Fuad Masduqi (Dian Nuswantoro Semarang, 2022)
Staphylococcus aureus is one of the pathogenic bacterial species. Pletekan plant has potential as a medicinal plant. This plant contains secondary metabolites and has been shown to have an antibacterial effect. The purpose of this study was to determine whether the peel off gel mask pletekan leaf extract could inhibit the growth of Staphylococcus aureus and whether there was a difference in the antibacterial activity of the peel off gel mask pletekan leaf extract at concentrations of 20%, 25%, and 30%. This research used maceration extraction method, phytochemical filtering and TLC. Peel off gel mask formulation from extracts with different concentrations. Furthermore, the research was carried out to test the antibacterial activity by using the well-drilled method on the peel off gel mask of pletekan leaf extract (Ruellia tuberosa L.) against the growth of Staphylococcus aureus. The results of screening and TLC showed pletekan leaf extract containing flavonoids, steroids, triterpenoids, and alkaloids. The peel off gel mask preparation test includes organoleptic, pH, homogeneity, adhesion, dispersion and drying time included in the Indonesian National Standard Criteria. The results showed that pletekan leaf extract (Ruellia tuberosa L.) in a peel off gel mask could inhibit the growth of Staphylococcus aureus. The results of statistical tests showed that the data were normally distributed and homogeneous. There was a significant difference in antibacterial activity in the peel off gel mask of pletekan leaf extract with concentrations of 20%, 25% and 30%, which were 4.323mm; 5.218mm; and 6.509mm. The antibacterial activity showed that the concentration was directly proportional to the resulting inhibition zone.